CARDIOVASCULAR RESPONSES TO SCALP INFILTRATION, USING ADRENALINE, WITH OR WITHOUT LIGNOCAINE, DURING CRANIOTOMY - Tariq, Muhammad Abbas; Kamran, Muhammad; Ali, Mumtaz (Journal of Postgraduate Medical Institute, 2011)
Objective: Material and Methods: Results: Conclusion: In neurosurgical patients undergoing craniotomy, infiltration of the scalp with solution containing adrenaline alone causes significant hypertension. The addition of lignocaine attenuates the hypertensive response but causes decrease in blood pressure. Episodes of tachycardia occurred more frequently in group B. Systolic blood pressure, diastolic blood pressure and mean arterial pressure were significantly increased in group B. Significant decrease in diastolic blood pressure and mean arterial pressure occurred in group A. This comparative study was carried out at AIMS international hospital Hayatabad, Peshawar from January to June 2009. Cardiovascular response to scalp infiltration with adrenaline was noted in 100 unpremedicated patients undergoing craniotomy. They were divided into 2 groups of 50 patients each. Group A received lignocaine 2% with adrenaline 1:200,000 and Group B received normal saline with adrenaline 1:200,000. To find out changes in the heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure after infiltrating scalp with adrenaline with or without Lignocaine in craniotomies.